2020
DOI: 10.3390/jmse8080620
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds, Intact and Processed, as a Valuable Component of Poultry Feeds

Abstract: Poultry production is an important area of the agricultural economy. Nowadays, there is an interest in novel sources of feed additives that will improve production performance and poultry health. As an easily available and renewable biomass rich in biologically active compounds, seaweeds can meet this demand. Different forms of seaweeds–seaweed powder from naturally occurring biomass, cultivated or waste biomass, extracted compounds, post-extraction residues or liquid extracts–may be used in poultry feeding. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 79 publications
1
46
0
1
Order By: Relevance
“…Such enhancement of supplementation may be due to the synergetic effects of organic Zn and Se and they have a potential nutritive value as feed additives for growing rabbits under summer heat stress conditions. Furthermore, confirmation is associated with the use of Spirulina which can improve the growth performance because it has some natural constituents such as phycocyanin, beta-carotene, tocopherols, linolenic acid, minerals, vitamins and phenolic compounds that had been shown to have strong antioxidant properties with promote growth and maintain health (Michalak and Mahrose [ 15 ] and Farag et al [ 16 ]. It has very high content of macro and micronutrients, essential amino acids, proteins, lipids, vitamins, minerals and anti-oxidants Soni et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such enhancement of supplementation may be due to the synergetic effects of organic Zn and Se and they have a potential nutritive value as feed additives for growing rabbits under summer heat stress conditions. Furthermore, confirmation is associated with the use of Spirulina which can improve the growth performance because it has some natural constituents such as phycocyanin, beta-carotene, tocopherols, linolenic acid, minerals, vitamins and phenolic compounds that had been shown to have strong antioxidant properties with promote growth and maintain health (Michalak and Mahrose [ 15 ] and Farag et al [ 16 ]. It has very high content of macro and micronutrients, essential amino acids, proteins, lipids, vitamins, minerals and anti-oxidants Soni et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase helps in protecting cellular membranes from oxidative damage which resulted in enhancing the growth performance of rabbits under hot conditions [ 51 ]. Recent literature have shown that Spirulina has an antioxidant, immunomodulatory, anti-inflammatory, antiviral, and antimicrobial activity in various experimental animals [ 15 , 40 , 52 ]. In this respect, Park et al [ 52 ] suggested that dietary Spirulina supplementation at levels of 0.25, 0.5, 0.75, or 1.0% in broiler diets caused an increase in the serum SOD, and GSH-Px activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ban forced industry professionals to search for alternative natural solutions [25]. Thanks to the prebiotic effects of algae oligosaccharides, algae can be part of the solution [24].…”
Section: Introductionmentioning
confidence: 99%
“…Among the algae, Spirulina platensis (Arthrospira platensis) stands out, a blue-green, unicellular alga with nutraceutical, probiotic, antioxidant, anti-inflammatory, hypolipidemic, hypoglycemic, antihypertensive, and immunomodulatory properties [16][17][18]. Spirulina has been shown to be an efficient dietary supplement for weight control in animals and humans, due to its excellent nutritional profile and the large amount of protein elements, phycocyanin, carotenoids, and all important amino acids for the body's balance [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%